If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = -3x + 6 Reorder the terms: -15 = 6 + -3x Solving -15 = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -15 + 3x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 -15 + 3x = 6 + 0 -15 + 3x = 6 Add '15' to each side of the equation. -15 + 15 + 3x = 6 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 6 + 15 3x = 6 + 15 Combine like terms: 6 + 15 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| -2x+5(8x-6)=9-x | | -12=8+(f/2) | | 24x+4+2=3(10x-1) | | 2/3p+1/2=p-3 | | 6(x+3)-(4x-4)= | | (x+9)(x-3)=(x+1) | | 8(-8+5b)+6=222 | | 5+5p=-30 | | 5n-(9-5n)=9 | | 2(x+3)=8(x-1) | | 21q+73=62q-51+8q | | B=(d/1-r) | | 8n+21n=-3 | | (25/8)(24/5) | | 3x-(x+1)=7 | | X+5+x+14=15 | | 3x+2y-5=ax+by+1 | | -144=-3-3(5+6k) | | 84x^2-238x-196=0 | | 7n+12=32 | | (25/8)(2/5) | | 24-x/3=6 | | 5(3x-5)=6(x-2)-19 | | (4n/7)+(3n/2)=-3 | | (12n+20)-4-8n=6-2n | | 3x^2+40x+112=0 | | 3/4x-1/4x=-11 | | 25/8*2/5 | | -13+5x=12 | | 1/(14-3x)=2/(5x+4) | | 0.7t=0.3+0.9t | | 2p+5r=a |